Quantitative resistance to crown rust: the role of its components for breeding varieties - Martinelli, José Antônio; Chaves, Márcia Soares; Federizzi, Luiz Carlos (MTT, 2004)
Selection of genotypes for quantitative resistance to oat crown rust based on its components needs the knowledge of the association of these components with each other and with the amount of disease in the field, represented by AUDPC. This work aimed to determine these correlations, based on results of previous trials, in which the reaction of 31 white oat genotypes was tested and the resistance components were quantified. Correlations were usually low, among the resistance components with each other as well as the components with the amount of disease in the field. Higher correlations with AUDPC, and consistent among years, were infection frequency in seedlings and latent period and pustule size in adult plants. All other possible correlations were very low. These data suggest that the resistance components mentioned can influence the expression of quantitative resistance in field in a slightly more important manner. Nevertheless, low correlation of resistance components with each other indicates that genotype selection, in this hostpathogen interaction, must not be accomplished on the basis of a single resistance component assessment. The correlation analysis suggests that the expression of quantitative resistance to oat crown rust is not conditioned by a single resistance component only but by the group effect of all of them. In addition, it is possible that different mechanisms are involved in each genotype, in a way that the more important resistance component in one genotype may not be the same in another.
Keywords: Ka; Puccinia coronata f. sp.; avenae; Avena sativa; phenotypic selection for resistance; partial resistance; slow rusting